Comparison of hand surgery in the German and Italian DRG systems Vergleich der Handchirurgie im deutschen und italienischen DRG-System - Lotter, O.; Dolderer, Jürgen H.; Stahl, S.; Atzei, A.; Haerle, M.; Schaller, H. E. (Gesundheitswesen, 2011)
Diagnosis-related groups (DRGs) are a patient classification system grouping related types of patients treated to the resources they consumed. In this analysis we compared the Italian and the German DRG systems regarding hand surgery with an emphasis on reimbursement of clinical cases. The 15 most common hand surgical diagnoses and their corresponding operative treatment in our clinic in 2009 were processed using a DRG grouper. The underlying data were transferred to the Italian system. Thus, the length of stay and the reimbursement of both countries could be obtained and compared. The latter was adjusted and corrected by the purchasing power of each country. The mean of the upper threshold of length of stay was 10 days in the German as well as the Italian system whereas the median was 2 times higher in Italy (6 vs. 12 days). Fifteen out of 19 cases showed higher reimbursement in Germany. The case mix index (CMI) of 0.917 in Germany represents a mean payment of 2676 per case. In Italy the hypothetical CMI of 0.635 resulted in a mean reimbursement of 1853 per case. The biggest difference in remuneration could be found for replantation of multiple fingers. For this service the German health-care system pays 12320 more than the Italian. Total proceeds of the top 15 diagnoses applying the number of cases treated in our clinic revealed 1.7 million in the German and 1.2 million in the Italian DRG system. Considering the purchasing power utilizing consumer prize parities, the difference of reimbursement between the countries decreased to 300000. There is no mean length of stay per DRG in Italy, only the upper threshold of length of stay is determined. In most cases the latter is higher in Italy compared to Germany. The consumption of resources for finger replantation is not adequately represented in the Italian DRG system compared to finger amputation. Reimbursement of inpatient care is influenced by multiple factors not being subject to the free market economy. For this reason only descriptive comparison is feasible. © Georg Thieme Verlag KG Stuttgart - New York.
CRIS-Team Scopus Importer:2024-12-11
Keywords: Diagnosis-related groups; Germany; Hand Surgery; Italy